Elevated serum interleukin-6 is predictive of coronary artery disease in intermediate risk overweight patients referred for coronary angiography - Wainstein, Marco V. (Diabetol Metab Syndr, 2017)
BACKGROUND: Interleukin-6 (IL-6) plays a central role in atherosclerosis and inflammation. It may improve risk prediction in patients at intermediate cardiovascular risk. OBJECTIVE: To analyze the impact of serum IL-6 in predicting early angiographic coronary artery disease in patients at intermediate cardiovascular risk with chest pain. METHODS: In a cross-sectional study, patients referred for coronary angiography due to suspected coronary artery disease (CAD) were included. Coronary artery disease was defined as the presence of at least 30% stenosis in one or more coronary artery. Severity of CAD was classified by the anatomic burden score. Performance of serum IL-6 assay was compared with ACC/AHA atherosclerotic cardiovascular disease (ASCVD) risk score and hs-CRP through receiver operating characteristic (ROC) curves. RESULTS: We have included 48 patients with a mean 10-year ASCVD risk of 10.0 ± 6.8%. The prevalence of CAD was 72.9%. The presence of CAD was associated with higher mean levels of IL-6 (p = 0.025). Patients with CAD had significantly more overweight than subjects without CAD. In 27% of patients, IL-6 was >1.0 pg/mL and 100% of these patients had CAD, while only 64% in those with IL-6 <1.0 pg/mL, corresponding to a positive predictive value of 100% (p = 0.015). The area under the receiver operating characteristic (ROC) curve of IL-6, hs-CRP and ASCVD were respectively 0.72, 0.60 and 0.54. Intermediate risk patients with IL-6 >1.0 pg/mL were further reclassified into ASCVD high risk due to the presence of coronary lesions. CONCLUSION: In intermediate risk patients referred for coronary angiography, a serum IL-6 level above 1 pg/mL is predictive of significant CAD. IL-6 determination may be useful to reclassify ASCVD intermediate risk patients into higher risk categories.